KAJIAN KRITIS TERHADAP KELOMPOK MATA KULIAH PRODI DKV USAKTI UNTUK POSIBILITAS KONEKTIVITAS ANTAR SILABUS: CRITICAL REVIEW OF USAKTI DKV STUDY PROGRAM COURSE GROUPS FOR POSSIBILITY OF CONNECTIVITY BETWEEN SYLLABI - Dikdik Adikara Rachman; Yosua Reydo Respati; Tommy M. Prihartanto; Januar Ivan (Universitas Trisakti, 2025)
Critical Review of Usakti DKV Study Program Course Groups for Possibility of Connectivity Between Syllabi. The major curriculum change in 2023 is seen as a momentum to conduct a critical review of all course groups. These course groups are considered as an important foundation to strengthen the connectivity between syllabi. The results of the critical review are prepared as constructive material to face future curriculum changes, both minor and major. The possibility of connectivity in the context of DKV learning is believed to contribute to the framework of strengthening teaching materials that are comprehensive and non-territorial between one course and another, so that students gain better understanding and learning experiences. Another result of this research is to offer the uniqueness of DKV in all practical courses. The research uses a qualitative descriptive method and was conducted in 2024 within the scope of the DKV study program, FSRD Universitas Trisakti.